2022
DOI: 10.1038/s41401-022-00949-9
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of toxoflavin, a potent IRE1α inhibitor acting through structure-dependent oxidative inhibition

Abstract: Inositol-requiring enzyme 1α (IRE1α) is the most conserved endoplasmic reticulum (ER) stress sensor with two catalytic domains, kinase and RNase, in its cytosolic portion. IRE1α inhibitors have been used to improve existing clinical treatments against various cancers. In this study we identified toxoflavin (TXF) as a new-type potent small molecule IRE1α inhibitor. We used luciferase reporter systems to screen compounds that inhibited the IRE1α-XBP1s signaling pathway. As a result, TXF was found to be the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Toxoflavin was shown to be the key virulence factor of phytopathogenic bacteria, for example, Burkholderia glumae , acting as an electron carrier that sequesters electrons from the respiratory chain of the plant and transfers them to oxygen, thereby generating toxic hydrogen peroxide (Iqbal et al., 2021). Recently published study suggested that toxoflavin can be useful as a molecular tool to study enzymes involved in sensing endoplasmic reticulum stress (Jiang et al., 2023).…”
Section: Bacterial Endophytes Of Medicinal Plants and Their Secondary...mentioning
confidence: 99%
“…Toxoflavin was shown to be the key virulence factor of phytopathogenic bacteria, for example, Burkholderia glumae , acting as an electron carrier that sequesters electrons from the respiratory chain of the plant and transfers them to oxygen, thereby generating toxic hydrogen peroxide (Iqbal et al., 2021). Recently published study suggested that toxoflavin can be useful as a molecular tool to study enzymes involved in sensing endoplasmic reticulum stress (Jiang et al., 2023).…”
Section: Bacterial Endophytes Of Medicinal Plants and Their Secondary...mentioning
confidence: 99%
“…In addition, toxoflavin can target the junction between the RNase and kinase domains and inhibit IRE1α by oxidizing the conserved cysteine residues in the active site of IRE1α, inhibiting its activity through oxidation of conserved cysteine residues within its active site. This property enables its application as a small molecule tool to investigate the involvement of IRE1α in ER stress 26 .…”
Section: Introductionmentioning
confidence: 99%